Pemberian Buah Kurma Meningkatkan Kadar Hemoglobin pada Ibu Hamil - Pratiwi, Sintia Diana; Triani, Yuyun (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2024)
Anaemia, a common condition during pregnancy, has been found to be associated with various factors such as physiological changes occurring during pregnancy, gestational fetal age and medical history of the pregnant woman. The current study was conducted to investigate the potential impact of consuming dates on the elevation of haemoglobin levels in pregnant women undergoing treatment at the Barokah Pajang Clinic. Employing an experimental design with pretest and posttest measurements using a control group, the study followed a quantitative approach. The sample collection method used was non-probability sampling, specifically sequential sample collection. The collected data was analyzed using the independent sample t-test, which revealed that pregnant women with anaemia who consumed dates experienced a statistically significant increase in haemoglobin levels at the Barokah Pajang Clinic. The findings suggest that taking iron supplements and consuming seven dates on an empty stomach for a week can help improve haemoglobin levels among pregnant women with anaemia. The P-value of 0.049 indicates the statistical significance of the results. This study highlights the potential benefits of a dietary intervention for pregnant women with anaemia, and it is recommended that they follow this regimen to ensure healthy pregnancies.